2022
DOI: 10.1186/s12944-022-01752-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a novel model to predict the risk of non-alcoholic fatty liver disease among lean pre-diabetics with normal blood lipid levels

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) has been associated with type 2 diabetes, but its relationship with pre-diabetes is still unknown. This study aims to determine whether pre-diabetes is associated with NAFLD, followed by establishing a NAFLD predictive nomogram for lean Chinese pre-diabetics with normal blood lipids. Methods Datasets from 3 previous studies, 1 (2774 pre-diabetics with normal blood lipids for training, 925 for val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…The direction of these correlations aligns with the definition of metabolic syndrome, with the strongest correlations observed for waist circumference and lipid levels. Many studies have previously shown the associations between waist circumference and lipid levels with liver diseases [ 39 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The direction of these correlations aligns with the definition of metabolic syndrome, with the strongest correlations observed for waist circumference and lipid levels. Many studies have previously shown the associations between waist circumference and lipid levels with liver diseases [ 39 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…более высокая концентрация АЛТ в крови. Предполагается, что в данном случае имеет место взаимосвязь НАЖБП и АЛТ не столько с ОДСН (NT-proBNP), сколько более высоким ИМТ и большей ОТ [13]. Но полученные результаты требуют подтверждения на большей выборке больных.…”
Section: Discussionunclassified
“…Compared to existing studies on prognosis prediction models, the predictive performance of the model developed in our study demonstrates certain advantages. In a study by Zhu et al, multivariate LR model was constructed to predict the risk of NAFLD among lean pre-diabetics with normal blood lipid levels, achieving an AUC of 0.796 in the longitudinal internal validation with a 5-year follow-up period [ 21 ]. Abeysekera et al utilized variables measured at the participants' adolescence to predict the incidence risk of NAFLD at the age of 24 using LR, yielding the highest AUROC of 0.79 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%